The functional and pasting properties of unripe plantain flour, and the sensory attributes of the cooked paste (amala) as affected by packaging materials and storage periods - Wasiu Awoyale; Hakeem Oyedele; Busie Maziya-Dixon (Cogent Food & Agriculture, 2020)
Unripe plantain flour (UPF) is hygroscopic and gets spoilt if not correctly processed, packaged and stored. Thus, the need to study the functional and pasting properties of the UPF, and the sensory attributes of the cooked paste (amala) as affected by packaging materials and storage periods. The UPF was produced using the standard method, packaged in a polypropylene woven sack (PPS) and polyvinyl chloride container (PVC), stored for 20-weeks at room temperature and analyzed at 4-weeks intervals. Results showed that the solubility index of UPF packaged in PPS had a significant (p < 0.05) positive correlation with the breakdown viscosity (r = 0.90), and a negative correlation with moldability (r = −0.89), mouthfeel (r = −0.92) and the overall acceptability (r = —0.83) of the amala. The peak viscosity of the UPF packaged in PPS had a significant (p < 0.05) negative correlation with the stretchability (r = —0.93), mouldability (r = −0.88), mouthfeel (r = —0.83) and overall acceptability (r = −0.01) of the amala. The packaging materials and storage periods had significant effect (p < 0.05) on the mouldability of the amala. The overall acceptability was higher in the amala prepared from PPS packaged UPF compared to that of the PVC. Therefore, UPF should be stored in PPS to retain its sensory attributes.